Self‐Assembled Architectures with Segregated Donor and Acceptor Units of a Dyad Based on a Monopyrrolo‐Annulated TTF–PTM Radical1. Issue 24 (1st May 2015) - Souto, Manuel; Solano, Marta V.; Jensen, Morten; Bendixen, Dan; Delchiaro, Francesca; Girlando, Alberto; Painelli, Anna; Jeppesen, Jan O.; Rovira, Concepció; Ratera, Imma; Veciana, Jaume
Abstract An electron donor–acceptor dyad based on a polychlorotriphenylmethyl (PTM) radical subunit linked to a tetrathiafulvalene (TTF) unit through a π‐conjugated N‐phenyl–pyrrole–vinylene bridge has been synthesized and characterized. The intramolecular electron transfer process and magnetic properties of the radical dyad have been evaluated by cyclic voltammetry, UV/Vis spectroscopy, vibrational spectroscopy, and ESR spectroscopy in solution and in the solid state. The self‐assembling abilities of the radical dyad and of its protonated non‐radical analogue have been investigated by X‐ray crystallographic analysis, which revealed that the radical dyad produced a supramolecular architecture with segregated donor and acceptor units in which the TTF subunits were arranged in 1D herringbone‐type stacks. Analysis of the X‐ray data at different temperatures suggests that the two inequivalent molecules that form the asymmetric unit of the crystal of the radical dyad evolve into an opposite degree of electronic delocalization as the temperature decreases.